ADAPTIVE REUSE GUIDELINES ON WARENHUIS MEDAN AND URBAN HERITAGE ENVIRONMENT - Winata, Denny; Tobing, Rumi Rosaline; Herwindo, Rahadhian Prajudi (Universitas Telkom, 2023)
Heritage buildings indicate the rich history of Indonesian civilization by its relation to history, culture, politics, and economics. Warenhuis as a class A heritage building within Medan’s historic district, play an important role in trading commodity. It possesses immense historical and cultural significancedespite being poorly maintained and neglected. The building suffered serious damage due to a fire outbreakand has not been revitalized. Furthermore, the adaptive reuse approach provides development guidelines that preserve and optimize the historic building’s tangible and intangible qualities. Urban regeneration guidelinesfor the surrounding heritage environment also need to be maintained to maintain the spatial qualityof Warenhuis Medan. Adaptive reuse is implemented in the revitalization of historical architecture andtheregeneration of Medan’s Warenhuis environment. This qualitative study uses case studies research method to produce revitalization guidelines on Medan’s Warenhuis and development guidelines on its historical urban spaces. Theoretical foundations, such as building adaptation theory, heritage regulations, and trading city concept are used to dissect case studies. Battersea Arts Centre and Beloit College Powerhouse. Objectives of this research are to formulate and to implement adaptive reuse concept in the revitalization of Warehuisarchitecture and the development of its historic environment. Theoretical reference in this study includesbuilding adaptation theory and heritage law that are used to analyse case studies Battersea Arts Centre andBeloit College Powerhouse. The objectives are to formulate and to adapt adaptive reuse in revitalize Warenhuis and its surrounding environment. The objectives were achieved by identifying Warenhuis’ urban context and heritage characteristics based on four factors in adaptation building: legal & economy, culture&social, and built environment. Research findings generates 7 points of heritage revitalization guidelines on Warenhuis and 12 points of guidelines in its urban regeneration. Keywords : adaptive reuse, building adaptation, heritage, Medan’s Warenhuis